Integrasi Islam Dalam Politik Kedatuan Suppa Abad 17 Masehi - Syaukani, Ahmad Nur; siri, Hasnani; Yani, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2024)
The aim of this research is to describe and analyze how Islam was integrated into the politics of the Suppa Chiefdom in the 17th century AD. This research is historical research, while the research approaches used are history (historical), anthropological approach and sociological approach. The research steps used are heruistics, source criticism, interpretation, historiography. The results of this research show that the role of the king in the Islamization of the Suppa Chiefdom in the 17th century AD was very important. After Datu Suppa said the two sentences of the creed, he invited all his family and community to embrace the teachings of Islam. Because of the Suppa people's belief that the king is an incarnation of god, this makes it easy for a king to control the community to embrace Islam. Islam also influenced the government structure in the Suppa Chiefdom. In the XVI century AD, the structure of the Limae Ajatappareng kingdom, especially the Suppa Chiefdom, was preceded by the King, then Pabcepatan, Matoa and below him, namely Arung Lili', Pakkaja, Passari, Paggalung, Pabbalu-balu, Paddare and Paddengeng, Pangonroang Ongko/ Ale' Karaja . However, after Islam became the official religion of the Suppa kingdom in 1609 AD, a new bureaucratic institution was formed with the name Parewa Syara', headed by a Qadhi. Since Islam was accepted in Kedatuan Suppa as the kingdom's religion, the meaning of sara' (Islamic law), has been integrated into the pannggadereng system (a form of Bugis-Makassar culture).